Urban sprawl and energy use for transportation in the largest Brazilian cities - da Silva, Antônio Nélson Rodrigues; Costa, Guilherme Camargo Ferraz; Brondino, Nair Cristina Margarido [UNESP] (Elsevier, 2007)
A study of the relationships between the amount of energy consumed for transportation purposes and a few selected variables related to urban form and socioeconomic characteristics of some of the largest Brazilian cities is conducted in this work. The studied cities include all 27 state capitals regardless of their size and population and 184 urban areas each with more than 20,000 inhabitants located in the state of São Paulo. Two different techniques were applied for data analyses: a more traditional regression analysis approach and artificial neural networks. In general, the results found in the analyses conducted here support the assumption that urban sprawl increases the energy use for transportation. In the case of the 27 state capitals, the analysis indicated that two spatial variables have a strong impact on the energy consumed for urban transportation: urban density and the ratio between the longest distances in the east-west and north-south directions. In the case of the 184 urbanized areas we also reached a similar conclusion. In that case, however, income and employment level apparently have a stronger influence on the amount of energy consumed. The results of the present study stress the importance of physical planning in developing country cities in order to reduce energy use for transportation. © 2007 International Energy Initiative, Inc.
Keywords: artificial neural network; developing world; employment; energy conservation; energy use; urban transport; Brazil; Sao Paulo [Brazil]; South America